A thermal model of hybrid cooling systems for building integrated semitransparent photovoltaic thermal system. (1st September 2017) - Gupta, Neha; Tiwari, Arvind; Tiwari, G.N.
Highlights: Building integrated semitransparent photovoltaic thermal (BiSPVT) system. Passive cooling of buildings. Evaporative cooling, natural ventilation and day light savings. Abstract: In today's world, most buildings are dependent on artificial cooling and artificial lighting, thus, increasing electrical consumption. This increases the emission of greenhouse gases which leads to environmental degradation. To reduce the dependence on the electrical grid and reduce the energy consumption for cooling the buildings, there is a need to apply passive and/or hybrid cooling systems to maintain the indoor thermal conditions. Evaporative cooling, ventilation, daylighting are examples of such systems. The paper makes an attempt to develop a thermal model of passive cooling systems (evaporative cooling, natural ventilation, daylight and heat storage capacity of materials) for building integrated semitransparent photovoltaic thermal systems and discusses their relevance in present day scenario. These concepts are effective in controlling the indoor room temperature by 30.16 °C decrease. The day light at the same time also helps enhance human performance. Impact of packing factor on room air temperature, solar cell temperature, floor temperature, solar cell efficiency and daylight savings has also been studied.